High strength steel plate and method for manufacturing same
By controlling the microstructural composition and phase distribution in hot-rolled steel sheets, the challenge of achieving high tensile strength while maintaining excellent ductility, fatigue strength, and punching properties is addressed, resulting in a high-strength steel sheet suitable for automotive applications.
Patent Information
- Application Number
- JP2024556691
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-07-26
- Filing Date
- 2024-07-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-07-09
AI Technical Summary
Existing technologies have not established a method for producing high-strength hot-rolled steel sheets with a tensile strength of 980 MPa or more, while maintaining excellent ductility, fatigue strength, and punching properties.
The solution involves controlling the area ratio of soft granular bainite and upper bainite near the Bs point, limiting the hard second phase, fresh martensite, and residual austenite phases to less than 15%, and optimizing the crystal grain size and component segregation to achieve a balance between strength and ductility.
This approach results in a high-strength steel sheet with a tensile strength of 980 MPa or more, exhibiting excellent ductility, fatigue strength, and punching properties, making it suitable for automotive parts without compromising safety or durability.
Smart Images

Figure 0007666761000004 
Figure 0007666761000001 
Figure 0007666761000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-strength steel sheet (particularly, a hot-rolled steel sheet) suitable for use as an automobile component, which has improved fatigue resistance and punchability in addition to strength and ductility, and to a method for producing the same. [Background technology]
[0002] In recent years, from the perspective of protecting the global environment, there has been a demand for a reduction in CO2 emissions on a global basis. In particular, there is a strong demand for improved fuel efficiency in automobiles, and there is a trend toward lighter automobile bodies. Increasing the strength of steel plates, which are the raw material for automobile parts, and reducing their thickness is one effective way to reduce the weight of automobile bodies without decreasing their strength. In particular, steel plates with a tensile strength of 980 MPa or more are expected to be a material that can dramatically improve automobile fuel efficiency through thinner thickness.
[0003] On the other hand, increasing the tensile strength of a steel sheet reduces its ductility, which deteriorates its press formability. Automobile parts, particularly suspension parts and other undercarriage parts, need to be formed into complex shapes to ensure rigidity, so materials for automobile parts are required to have high press formability, particularly excellent ductility.
[0004] Furthermore, in order to ensure durability that decreases with the thinning of automotive parts, it is necessary to improve the fatigue strength of steel plates. Automotive parts, particularly suspension parts and other undercarriage parts, are repeatedly loaded by tires, so if the fatigue strength is low, the durability of the parts may fall short of what was expected in the design as the driving distance increases. However, generally, increasing the strength of steel plates does not necessarily increase fatigue strength, and in addition, increasing the strength of materials makes it easier for defects with unevenness to occur on the punched end surface, which then initiates cracks, leading to deterioration of fatigue resistance properties.
[0005] Thus, in steel sheets having a tensile strength of 980 MPa or more, excellent fatigue strength and punchability are required in addition to excellent ductility. Various studies have been conducted to improve the fatigue strength and punchability while increasing the tensile strength of steel sheets (Patent Documents 1 to 3).
[0006] Patent Document 1 discloses a technology relating to a high-strength hot-rolled steel sheet having excellent formability and fatigue resistance by controlling the manufacturing conditions of hot rolling, making the main phase ferrite, and controlling the shape and dispersion form of inclusions.
[0007] Patent Document 2 discloses a technique relating to a high-strength hot-rolled steel sheet that is excellent in punching fatigue resistance and formability by controlling the shape and hardness of martensite in the center of the sheet thickness.
[0008] Patent Document 3 discloses a technology relating to a high-strength hot-rolled steel sheet having excellent hole expandability and punchability, which is achieved by controlling the manufacturing conditions of the hot rolling, making the main phase bainite, and controlling the shape and dispersion form of the hard second phase as well as the amount of precipitates. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2014-31560 A [Patent Document 2] JP 2015-214718 A [Patent Document 3] Republished Publication No. 2017-017933 Summary of the Invention [Problem to be solved by the invention]
[0010] However, the conventional techniques described in Patent Documents 1 to 3 have the following problems.
[0011] The techniques described in Patent Documents 1 and 2 fail to achieve a tensile strength of 980 MPa or more.
[0012] The technology described in Patent Document 3 provides a hot-rolled steel sheet having a tensile strength of 980 MPa or more, excellent fatigue strength, and excellent punchability. The technology described in Patent Document 3 provides a hot-rolled steel sheet having a tensile strength of 980 MPa or more, excellent punchability, and excellent hole expandability. However, the technology does not mention the fatigue strength, which is the subject of the present application, and does not necessarily provide good fatigue strength.
[0013] As described above, in the prior art, there is no established technology for producing a high-strength hot-rolled steel sheet having a tensile strength of 980 MPa or more and excellent ductility, fatigue strength and punchability.
[0014] Therefore, an object of the present invention is to provide a high-strength hot-rolled steel sheet having a tensile strength of 980 MPa or more and excellent ductility, fatigue strength and punchability, and a manufacturing method thereof.
[0015] In the present invention, excellent ductility means having a uniform elongation of 6.0% or more. Also, excellent fatigue strength means a fatigue strength of 2×10 to tensile strength in a plane bending test with a stress ratio of -1. 6 It means that the ratio of the plane bending fatigue strength at times the bending moment (fatigue limit ratio) is 0.50 or more. In addition, excellent punchability means that when punched with a 10mmφ punch at three or more clearances including 10% and 20% within the clearance range of 10 to 20%, there are no cracks, chips, brittle fracture surfaces, or secondary shear surfaces on the edge of each punched hole. [Means for solving the problem]
[0016] In order to achieve the above object, the inventors have conducted extensive research to improve the ductility, fatigue strength, and punchability of hot-rolled steel sheets while maintaining a tensile strength of 980 MPa or more. As a result, the main phase is bainite, and the area ratio of soft granular bainite and upper bainite generated near the Bs point is controlled within a certain range, and the hard second phase, fresh martensite and retained austenite phase, is set to less than 15%. In addition, segregation is reduced by setting the difference |Hv1-Hv2| between the hardness Hv1 at the 1 / 2 position of the sheet thickness and the hardness Hv2 at the 1 / 4 position of the sheet thickness to 30% or less for 0.3TS (MPa). Furthermore, the average crystal grain size of the upper bainite is set to 7 μm or less. It has been found that these make it possible to obtain a steel sheet having excellent ductility, fatigue strength, and punchability while maintaining a tensile strength of 980 MPa or more.
[0017] The upper bainite phase herein refers to an aggregate of lath-shaped bainitic ferrite, specifically, a structure having Fe-based carbides and / or a retained austenite phase between lath-shaped bainitic ferrite.
[0018] Lath-like bainitic ferrite differs from lamellar (layered) ferrite and polygonal ferrite in pearlite in that it has a lath-like shape and a relatively high dislocation density internally, making the two distinguishable using a scanning electron microscope (SEM) or transmission electron microscope (TEM).
[0019] In addition, when there is a residual austenite phase between the laths, only the lath-shaped bainitic ferrite portion is regarded as upper bainite and is distinguished from the residual austenite phase. Fresh martensite is martensite that does not contain Fe-based carbides.
[0020] Granular bainite is composed of granular bainitic ferrite and means a structure having Fe-based carbides and / or residual austenite phase between the granular bainitic ferrite. The aspect ratio is 2 or less, and the grains have grain boundaries that do not have the orientation relationship of <axial direction>-rotation angle of <15 16 18>-60°, <6 15 15>-56°, <6 7 7>-50°, <1 0 1>-60°, and <1 2 2>-17°. The crystal orientation is obtained using the electron backscatter diffraction patterns (EBSD) method. Fresh martensite and / or residual austenite phase have low clarity (IQ value). Prior austenite grains have a large aspect ratio and large crystal grains, so in this study, crystal grains with an aspect ratio of 2 or more and a size of 10 μm or more were considered to be prior austenite grains. Therefore, upper bainite grains were excluded from the grains with misorientation of 15° or more, and among the remaining grains, grains with high IQ values and aspect ratios of 2 or less and 10 μm or less were judged to be granular bainite.
[0021] In addition, the fresh martensite and / or retained austenite phase has brighter contrast in the SEM image than the upper bainite phase, the lower bainite and / or tempered martensite phase, and the polygonal ferrite phase, and therefore the fresh martensite phase and / or retained austenite phase can be distinguished from these structures using SEM.
[0022] The fresh martensite and retained austenite phases have similar contrast in SEM, but can be distinguished from each other using electron beam reflection diffraction.
[0023] The present invention was made based on the above findings and further studies, and is summarized as follows. [1] The composition is, by mass%, C: 0.04-0.18%, Si: 0.1-2.5%, Mn: 1.0-3.0%, P: 0.1% or less, S: 0.01% or less, Al: 0.010-1.0%, and N: 0.01% or less, with the remainder being Fe and unavoidable impurities. The microstructure is mainly composed of bainite phase consisting of upper bainite and granular bainite at an area ratio of 85% or more, and fresh martensite. a hard second phase including granular bainite and / or retained austenite phase having an area ratio of less than 15%, an area ratio of granular bainite relative to the area ratio of upper bainite in the bainite phase being 5% or more and 40% or less, a difference |Hv1-Hv2| between the hardness Hv1 at 1 / 2 the plate thickness position and the hardness Hv2 at 1 / 4 the plate thickness position being 30% or less for 0.3TS, and an average crystal grain size of the upper bainite phase being 7 μm or less. [2] The high-strength steel plate according to [1], further comprising, in addition to the above-mentioned chemical composition, one or more of groups a to e, in terms of mass %, Group a: one or more selected from V: 0.005-0.5%, Ti: 0.005-0.2%, and Nb: 0.005-0.1%, Group b: one or more selected from Cu: 0.005-0.5%, Ni: 0.005-0.5%, Cr: 0.005-1.0%, and Mo: 0.005-0.5%, Group c: B: 0.0002-0.005%, group d: Sb: 0.001-0.1%, and Sn: 0.001-0.1%, one or two selected from group e: Ca: 0.0001-0.005%, Mg: 0.0001-0.005%, and REM: 0.0001-0.005%. [3] A method for producing a high-strength steel plate according to [1] or [2], comprising the steps of: casting a molten steel material having the above-mentioned composition while rotating it in a horizontal plane relative to a mold at a rotation speed of 10 cm / s or more by an induction electromagnetic stirrer; heating the obtained steel material to 1150°C or more; rough rolling the heated steel material to obtain a steel plate; finish rolling the steel plate under a finish rolling end temperature condition of (RC-50)°C or more and (RC+100)°C or less; and cooling the steel plate after the finish rolling from the end of the finish rolling. A manufacturing method of high strength steel sheet, comprising cooling under the conditions of: time to start of cooling: within 2.0 s, average surface cooling rate to Bs: 30°C / s or more, residence time at temperature between (Bs-100)°C and Bs°C: 3.0 s to 10.0 s, cooling stop temperature: between (Bs-250)°C and (Bs-100)°C, coiling the cooled steel sheet under the conditions of coiling temperature: between (Bs-250)°C and (Bs-100)°C, and cooling to (Bs-400)°C at an average cooling rate of 1°C / s or less. Note that RC and Bs are defined by the following formulas (1) and (2), respectively. RC(℃)=750+120×C+100×N+10×Mn+250×Ti+5000×B+10×Cr+50×Mo+750×Nb+150×V…(1) Bs(℃)=830-270×C-90×Mn-70×Cr-37×Ni-83×Mo-20×Cu…(2) Here, the symbols of the elements in the above formulas (1) and (2) represent the content (mass%) of each element, and are set to 0 when the element is not contained. Effect of the Invention
[0024] According to the present invention, it is possible to provide a high-strength steel sheet having a tensile strength of 980 MPa or more and excellent ductility, fatigue strength and punchability, and a manufacturing method thereof.
[0025] When the high-strength steel plate of the present invention is applied to automobile underbody parts such as suspensions, structural parts, frame parts, and truck frame parts, safety can be ensured and the weight of the automobile body can be reduced, which is extremely effective in industry. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a schematic diagram showing the shape of a test piece for a plane bending fatigue test in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, an embodiment of the present invention will be described. Note that the following description shows an example of a preferred embodiment of the present invention, and the present invention is not limited to the following embodiment.
[0028] The steel sheet has the following chemical composition: In the following description, "%" which is the unit of the content of an element in the chemical composition means "mass %" unless otherwise specified.
[0029] <C:0.04~0.18%> C is an element effective in promoting the formation of bainite by improving hardenability and improving strength. It also suppresses the formation of granular bainite by lowering the Bs point and transforming bainite at a lower temperature. If the C content is less than 0.04%, such effects are not sufficiently obtained, and a tensile strength of 980 MPa or more cannot be obtained. For this reason, the C content is 0.04% or more, preferably 0.05% or more, and more preferably 0.06% or more. On the other hand, if the C content exceeds 0.18%, a hard second phase including fresh martensite and / or retained austenite phase is excessively formed, and sufficient fatigue strength cannot be obtained. For this reason, the C content is 0.18% or less, preferably 0.17% or less, and more preferably 0.15% or less.
[0030] <Si:0.1~2.5%> Silicon strengthens steel through solid solution and contributes to improving the strength of steel. Therefore, the silicon content is 0.1% or more, preferably 0.3% or more, and more preferably 0.5% or more. On the other hand, silicon is an element that promotes the formation of ferrite, and if the silicon content exceeds 2.5%, ferrite is formed and the fatigue strength decreases. Therefore, the silicon content is 2.5% or less, preferably 2.3% or less, and more preferably 2.0% or less.
[0031] <Mn: 1.0~3.0%> Mn is an element that stabilizes austenite and is effective in suppressing the formation of ferrite and improving strength. Also, by lowering the Bs point and causing bainite to transform at a lower temperature, the formation of granular bainite is suppressed. When the Mn content is less than 1.0%, these effects cannot be fully obtained, ferrite and granular bainite are formed, and a tensile strength of 980 MPa or more and excellent fatigue strength cannot be obtained. For this reason, the Mn content is 1.0% or more, preferably 1.2% or more, and more preferably 1.5% or more. On the other hand, when the Mn content exceeds 3.0%, the amount of a hard second phase containing fresh martensite and / or retained austenite phase increases, and sufficient fatigue strength cannot be obtained. For this reason, the Mn content is 3.0% or less, preferably 2.8% or less, and more preferably 2.5% or less.
[0032] <P: 0.1% or less> Since P deteriorates weldability, it is desirable to reduce its amount as much as possible. In the present invention, a P content of up to 0.1% is acceptable. Therefore, the P content is set to 0.1% or less. The lower limit is not particularly defined, but if the P content is less than 0.003%, the refining cost increases, so the P content is preferably 0.003% or more, and more preferably 0.005% or more.
[0033] <S: 0.01% or less> Since S deteriorates weldability, it is preferable to reduce its amount as much as possible. In the present invention, an S content of up to 0.01% is acceptable. Therefore, the S content is set to 0.01% or less. The lower limit is not particularly defined, but if the S content is less than 0.0001%, the production efficiency decreases, so 0.0001% or more is preferable, and 0.0005% or more is more preferable.
[0034] <Al: 0.010~1.0%> Al acts as a deoxidizer and is an element effective in improving the cleanliness of steel. If the amount of Al is too small, the effect may not be sufficient. Therefore, the Al content is 0.010% or more, preferably 0.015% or more, and more preferably 0.020% or more. On the other hand, Al is an element that promotes ferrite formation. When the Al content rate exceeds 1.0%, ferrite is generated and the fatigue strength is reduced. Therefore, the Al content is 1.0% or less, preferably 0.8% or less, and more preferably 0.5% or less.
[0035] <N: 0.01% or less> N combines with elements that form nitrides and precipitates as nitrides, contributing to the refinement of crystal grains. However, N easily combines with Ti at high temperatures to form coarse nitrides, and excessive content reduces the fatigue strength. Therefore, the N content is 0.01% or less, preferably 0.008% or less, and more preferably 0.006% or less. The lower limit is not particularly specified, but if the N content is less than 0.001%, the production efficiency will decrease, so 0.001% or more is preferred.
[0036] The balance is Fe and inevitable impurities.
[0037] The above components are the basic component composition of the high-strength steel sheet of the present invention. If necessary, the following elements can be further contained.
[0038] V, Ti, and Nb are elements effective in forming carbides and improving strength by precipitation strengthening. Therefore, when V, Ti, and Nb are contained, the respective contents are preferably V: 0.005 - 0.5%, Ti: 0.005 - 0.2%, and Nb: 0.005 - 0.1%. When the contents of V, Ti, and Nb exceed the above upper limits respectively, the carbides may coarsen and the punching property may deteriorate. Therefore, the V content is preferably 0.05% or more, more preferably 0.1% or more, and more preferably 0.3% or less. The Ti content is more preferably 0.01% or more and more preferably 0.1% or less. The Nb content is more preferably 0.01% or more and more preferably 0.08% or less.
[0039] Cr, Ni, Cu, and Mo are elements that stabilize austenite, and are effective in suppressing the formation of ferrite and improving strength. In addition, they lower the Bs point and transform bainite at a lower temperature, thereby suppressing the formation of granular bainite. For this reason, when Cr, Ni, Cu, and Mo are contained, the respective contents are preferably set to Cr: 0.005 to 1.0%, Ni: 0.005 to 0.5%, Cu: 0.005 to 0.5%, and Mo: 0.005 to 0.5%. If the contents of Cr, Ni, Cu, and Mo exceed the respective upper limits, a hard second phase including fresh martensite and / or retained austenite phase is excessively formed, and the steel structure of the present invention may not be obtained. The Cr content is preferably 0.01% or more, more preferably 0.3% or more, and more preferably 0.8% or less. The Ni content is preferably 0.01% or more, more preferably 0.05% or more, and more preferably 0.3% or less. The Cu content is preferably 0.01% or more, more preferably 0.05% or more, and more preferably 0.3% or less. The Mo content is preferably 0.01% or more, more preferably 0.05% or more, and more preferably 0.3% or less.
[0040] When B is contained, it is preferably 0.0002 to 0.005%. B is an effective element for segregating to the austenite grain boundaries and suppressing the formation of ferrite, thereby promoting the formation of upper bainite and granular bainite, and further improving the strength of the steel sheet. In order to realize these effects, it is preferable that the B content is 0.0002% or more. Therefore, the B content is 0.0002% or more, preferably 0.0005% or more, and more preferably 0.0007% or more. On the other hand, when the B content exceeds 0.005%, the above effects are saturated. Therefore, the B content is 0.005% or less, preferably 0.004% or less, and more preferably 0.003% or less.
[0041] Sb is an element that is effective in suppressing the de-elementation from the surface of the steel material when the steel material is heated, and suppressing the decrease in the strength of the steel. Therefore, when Sb is contained, the content is preferably 0.001 to 0.1%. If the Sb content exceeds the above upper limit, it may cause embrittlement of the steel sheet. The Sb content is more preferably 0.005% or more, and more preferably 0.05% or less.
[0042] Sn is an element that is effective in suppressing the formation of pearlite and suppressing the decrease in strength of steel. In order to obtain such an effect, when Sn is contained, the content is preferably 0.001 to 0.1%. If the Sn content exceeds the above upper limit, it may cause embrittlement of the steel sheet. The Sn content is more preferably 0.005% or more, and more preferably 0.05% or less.
[0043] Ca, Mg, and REM are elements effective in improving punchability by controlling the shape of inclusions. In order to obtain such effects, when Ca, Mg, and REM are contained, the respective contents are preferably set to Ca: 0.0001-0.005%, Mg: 0.0001-0.005%, and REM: 0.0001-0.005%. On the other hand, if the Ca and REM contents exceed the above upper limits, the amount of inclusions increases and fatigue strength may deteriorate. The Ca content is more preferably set to 0.0005% or more and more preferably set to 0.003% or less. The Mg content is more preferably set to 0.0005% or more and more preferably set to 0.003% or less. The REM content is more preferably set to 0.0005% or more and more preferably set to 0.003% or less. REM (rare earth elements) is a collective term for Sc, Y, and 15 elements ranging from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71, and the REM content here refers to the total content of these elements. For each component of groups a to e (V, Ti, Nb, Cr, Ni, Cu, Mo, B, Sb, Sn, Ca, Mg, REM), if the content is less than the lower limit above, the component is considered to be included as an unavoidable impurity.
[0044] Next, the microstructure of the high strength steel plate of the present invention will be described.
[0045] The high-strength steel sheet of the present invention has the following microstructure. The main phase is a bainite phase consisting of upper bainite and granular bainite with an area ratio of 85% or more. The area ratio of a hard second phase including fresh martensite and / or retained austenite phase is less than 15%. In the bainite phase, the area ratio of granular bainite relative to the area ratio of upper bainite is 5% or more and 40% or less, and the average crystal grain size of the upper bainite phase is 7 μm or less. The difference |Hv1-Hv2| between the hardness Hv1 at 1 / 2 the sheet thickness position and the hardness Hv2 at 1 / 4 the sheet thickness position is 30% or less with respect to 0.3TS.
[0046] <Main phase: Bainite phase 85% or more> The microstructure of the high-strength steel plate of the present invention contains a bainite phase consisting of upper bainite and granular bainite as a main phase. If the bainite phase is less than 85% by area, excellent punchability cannot be obtained. Therefore, the bainite phase is set to 85% or more, preferably 90% or more, and more preferably 95% or more.
[0047] <Hard second phase: Fresh martensite and / or retained austenite phase less than 15%> If the hard second phase is controlled to be fresh martensite and / or retained austenite and the area ratio is less than 15%, no macroscopic stress concentration occurs at the phase interface during fatigue testing and no fatigue cracks will start to occur, resulting in excellent fatigue strength. For this reason, the area ratio of the hard second phase containing fresh martensite and / or retained austenite is set to less than 15%, preferably 10% or less, and more preferably 5% or less.
[0048] The remaining structure other than upper bainite, granular bainite, fresh martensite and / or retained austenite phase is permissible if it is 3% or less. Examples of the remaining structure include lower bainite, ferrite, tempered martensite, pearlite, etc.
[0049] <Area ratio of granular bainite to area ratio of upper bainite in the bainite phase is 5% to 40%> Granular bainite has better ductility than upper bainite. When the area ratio of granular bainite to the area ratio of upper bainite in the bainite phase is less than 5%, excellent ductility cannot be obtained. Therefore, the area ratio of granular bainite to the area ratio of upper bainite in the bainite phase is 5% or more, preferably 8% or more, and more preferably 10% or more. On the other hand, when the area ratio of granular bainite to the area ratio of upper bainite exceeds 40%, a significant deterioration in fatigue strength is caused. Therefore, the area ratio of granular bainite to the area ratio of upper bainite is 40% or less, preferably 35% or less, and more preferably 30% or less.
[0050] <Average grain size of upper bainite phase is 7μm or less> The grain boundaries have the effect of making it difficult for the slip deformation to propagate to adjacent grains, which results in improved fatigue strength. Therefore, the average grain size of the upper bainite phase is 7 μm or less, and preferably 6 μm or less. Although there is no particular lower limit, if the average grain size is too small, it may lead to a decrease in ductility, so the average grain size is preferably 1 μm or more, and more preferably 2 μm or more.
[0051] <The difference between the hardness Hv1 at 1 / 2 the plate thickness and the hardness Hv2 at 1 / 4 the plate thickness |Hv1-Hv2| is 30% or less for 0.3TS> When the segregation of components such as Mn becomes excessive at the 1 / 2 position of the sheet thickness, a hard second phase containing fresh martensite and / or a retained austenite phase is locally generated, and a difference in hardness occurs with the matrix structure, which makes it easy for cracks and roughness to occur during punching. When the difference |Hv1-Hv2| between the hardness Hv1 at the 1 / 2 position of the sheet thickness and the hardness Hv2 at the 1 / 4 position of the sheet thickness exceeds 30% with respect to 0.3TS, the punchability deteriorates significantly. For this reason, the difference |Hv1-Hv2| between the hardness Hv1 at the 1 / 2 position of the sheet thickness and the hardness Hv2 at the 1 / 4 position of the sheet thickness is 30% or less with respect to 0.3TS, preferably 25% or less, and more preferably 20% or less. There is no need to particularly limit the lower limit, and it may be 0%. In addition, TS is tensile strength. The measurements of the hardness Hv1, Hv2, and TS at this time are performed by the method shown in the examples.
[0052] The high-strength steel sheet of the present invention has a tensile strength of 980 MPa or more, and also has excellent ductility, excellent fatigue strength, and excellent punchability. Therefore, the high-strength steel sheet of the present invention has high tensile strength, and even when it is thinned, it ensures safety and can be applied to parts of trucks and passenger cars. In the present invention, the area ratios of each structure and the mechanical properties described above are values measured by the methods described in the Examples.
[0053] Next, a method for producing a high-strength steel plate according to an embodiment of the present invention will be described. In the following description, the temperature indicated in "°C" refers to the surface temperature of the object (steel material or steel plate) unless otherwise specified.
[0054] The high-strength steel plate of the present invention can be produced by sequentially carrying out the following treatments (1) to (6). Each step will be described below. (1) Melting and Casting (2)Heating (3) Hot rolling (4) Cooling (first cooling) (5) Winding (6) Cooling (second cooling) (1) Melting and Casting The method of producing the molten steel is not particularly limited. For example, the molten steel having the above-mentioned composition can be produced by a known method such as a converter to obtain the molten steel. Scrap may be used as the raw material. The obtained molten steel is made into a steel material by a continuous casting method. Induction electromagnetic stirring has the effect of reducing the segregation of components that occurs during solidification by dividing the columnar crystals growing from the mold and generating equiaxed crystals from the 1 / 4 to 1 / 2 plate thickness positions, and promotes the formation of granular bainite. If the rotation speed during electromagnetic stirring is less than 10 cm / s, the columnar crystals are not sufficiently divided and such an effect cannot be obtained. For this reason, the rotation speed is 10 cm / s or more in the horizontal plane, preferably 15 cm / s or more, and more preferably 20 cm / s or more.
[0055] On the other hand, the upper limit of the swirling speed during electromagnetic stirring is not particularly limited, but from the viewpoint of production, it is preferably 50 cm / s or less, more preferably 45 cm / s or less, and even more preferably 40 cm / s or less. After being produced by the continuous casting method, the steel material may be directly subjected to the subsequent heating step, or the steel material that has been cooled to become a hot or cold piece may be subjected to the heating step. Furthermore, the chemical composition of the finally obtained high strength steel plate is the same as that of the raw steel material used.
[0056] (2)Heating First, the steel material is heated to a heating temperature of 1150°C or higher. In the steel material after being cooled to a low temperature, most of the precipitate-forming elements are present in a non-uniform manner as coarse precipitates. If the additive elements are present as coarse and non-uniform precipitates, the effect of the additive elements is not fully obtained, and the desired steel structure is not obtained. Therefore, it is necessary to heat the steel material prior to hot rolling to dissolve the coarse precipitates. For this reason, the heating temperature of the steel material is 1150°C or higher, preferably 1180°C or higher, and more preferably 1200°C or higher. On the other hand, if the heating temperature of the steel material becomes too high, it will cause the occurrence of slab defects and a decrease in yield due to scale-off. For this reason, the heating temperature of the steel material is preferably 1350°C or lower, more preferably 1300°C or lower, and even more preferably 1280°C or lower. In terms of uniformizing the temperature of the steel material during heating, it is preferable to heat the steel material to the heating temperature and then hold it at the heating temperature. The time for which the steel material is held at the heating temperature (holding time) is not particularly limited, but from the viewpoint of increasing the temperature uniformity of the steel material, it is preferable to set the time to 1800 seconds or more. On the other hand, if the holding time exceeds 10000 seconds, the amount of scale generation increases. As a result, scale bite or the like is likely to occur in the subsequent hot rolling, leading to a decrease in yield due to poor surface defects. Therefore, the holding time is preferably set to 10000 seconds or less, and more preferably to 8000 seconds or less. Note that this heating step also includes a case where the steel material before hot rolling is directly subjected to hot rolling (direct rolling) while still at a high temperature (i.e., while maintaining a temperature within the above heating temperature range) after casting.
[0057] (3) Hot rolling Next, the heated steel material (or the steel material still at a high temperature after casting) is subjected to hot rolling, which includes rough rolling and finish rolling. The conditions of the rough rolling are not particularly limited as long as the desired sheet bar dimensions can be secured.
[0058] First, a steel material is roughly rolled to obtain a roughly rolled plate. Before the resulting roughly rolled plate is subjected to finish rolling, descaling (high-pressure water descaling) may be performed on the inlet side of a finish rolling mill by spraying high-pressure water thereon.
[0059] Next, in the present invention, when the temperature RC is defined by the following formula (1), the finish rolling end temperature is set to be (RC-50)°C or more and (RC+100)°C or less. RC is the lower limit temperature of austenite recrystallization estimated from the chemical composition. If the finish rolling end temperature is less than (RC-50)°C, strain is not easily relieved by recrystallization, and the austenite is cooled while strain is still accumulated, which excessively promotes the formation of granular bainite. For this reason, the finish rolling end temperature is (RC-50)°C or more, preferably (RC-30)°C or more, and more preferably RC°C or more.
[0060] On the other hand, if the finish rolling end temperature is higher than (RC+100)°C, the austenite grains become coarse and the average grain size of the upper bainite becomes large, so sufficient fatigue strength cannot be obtained. Therefore, the finish rolling end temperature is (RC+100)°C or less, preferably (RC+80)°C or less, and more preferably (RC+50)°C or less. RC is defined by the following formula (1). RC(℃)=750+120×C+100×N+10×Mn+250×Ti+5000×B+10×Cr+50×Mo+750×Nb+150×V...(1) Here, each element symbol in the above formula (1) represents the content (mass%) of each element, and if the element is not contained, it is set to 0.
[0061] (4) Cooling (first cooling) Next, the obtained hot-rolled steel sheet is cooled (first cooling). In this case, the time from the end of hot rolling to the start of cooling (cooling start time) is set to within 2.0 s after the end of finish rolling. If the cooling start time exceeds 2.0 s, the austenite grains become coarse and the average grain size of the upper bainite becomes large, so that sufficient tensile strength and fatigue strength cannot be obtained. For this reason, the cooling start time is set to within 2.0 s, preferably within 1.5 s, and more preferably within 1.0 s.
[0062] In addition, the average cooling rate on the surface from the finish rolling end temperature to Bs is 30°C / s or more. If the average cooling rate from the finish rolling end temperature to Bs is too slow, ferrite is excessively generated, and sufficient tensile strength and fatigue strength cannot be obtained. Therefore, the average cooling rate is 30°C / s or more, preferably 40°C / s or more, and more preferably 50°C / s or more. On the other hand, although there is no particular upper limit, if it is too fast, it becomes difficult to control the cooling stop temperature. Therefore, the average cooling rate is preferably 500°C / s or less, more preferably 300°C / s or less, and even more preferably 150°C / s or less.
[0063] Furthermore, in the cooling, the residence time at a temperature of (Bs-100)°C or more and Bs°C or less is set to 3.0 s or more and 10.0 s or less. If the residence time at a temperature of (Bs-100)°C or more and Bs°C or less is less than 3.0 s, granular bainite is not obtained sufficiently. Therefore, the residence time at a temperature of (Bs-100)°C or more and Bs°C or less is 3.0 s or more, preferably 4.0 s or more, and more preferably 5.0 s or more. If the residence time at a temperature of (Bs-100)°C or more and Bs°C or less exceeds 10.0 s, granular bainite is excessively generated and sufficient fatigue strength is not obtained. Therefore, the residence time at a temperature of (Bs-100)°C or more and Bs°C or less is set to 10.0 s or less, preferably 9.0 s or less, and more preferably 8.0 s or less.
[0064] In addition, the cooling method is not particularly limited as long as forced cooling is performed so as to obtain the above average cooling rate. The cooling stop temperature is (Bs-250)°C or more and (Bs-100)°C or less. If the cooling stop temperature is less than (Bs-250)°C, the microstructure becomes lower bainite. The lower bainite is a high-strength structure, but does not have excellent ductility. For this reason, the cooling stop temperature is (Bs-250)°C or more, preferably (Bs-220)°C or more, and more preferably (Bs-200)°C or more. On the other hand, if the cooling stop temperature is higher than (Bs-100)°C, granular bainite is excessively generated, and therefore excellent fatigue strength cannot be obtained. For this reason, the cooling stop temperature is (Bs-100)°C or less, preferably (Bs-120)°C or less, and more preferably (Bs-150)°C or less. Note that Bs is defined by the following formula (2). Bs(℃)=830-270×C-90×Mn-70×Cr-37×Ni-83×Mo-20×Cu...(2) Here, each element symbol in the above formula (2) represents the content (mass%) of each element, and elements that are not contained are represented as 0.
[0065] (5) Winding Next, the cooled hot-rolled steel sheet is coiled under the condition of a coiling temperature of (Bs-250)°C or more and (Bs-100)°C or less. If the coiling temperature is less than (Bs-250)°C, lower bainite and / or tempered martensite are generated, resulting in insufficient ductility. For this reason, the coiling temperature is (Bs-250)°C or more, preferably (Bs-230)°C or more, and more preferably (Bs-200)°C or more. On the other hand, if the coiling temperature is higher than (Bs-100)°C, granular bainite is excessively generated, and therefore excellent fatigue strength cannot be obtained. For this reason, the coiling temperature is (Bs-100)°C or less, preferably (Bs-120)°C or less, and more preferably (Bs-150)°C or less.
[0066] (6) Cooling (second cooling) Next, the steel is cooled to (Bs-400)°C or less at an average cooling rate of 1°C / s or less (second cooling). If the average cooling rate from the coiling temperature to (Bs-400)°C or less exceeds 1°C / s, lower bainite and / or tempered martensite will be generated, resulting in insufficient ductility. For this reason, the average cooling rate from the coiling temperature to (Bs-400)°C or less is 1°C / s or less, preferably 0.8°C / s or less, and more preferably 0.5°C / s or less. There is no particular reason for limiting the lower limit of the average cooling rate, but from the viewpoints of manufacturing efficiency and coarsening of carbides, 0.001°C / s or more is preferable. The cooling can be performed to any temperature below (Bs-400)°C, but it is preferable to cool to 50°C. The cooling can be performed in any form, for example, it may be performed in the state of a coiled coil.
[0067] The high strength steel sheet of the present invention can be manufactured by the above-mentioned procedure. After coiling and subsequent cooling, the steel sheet may be subjected to a conventional method. For example, the steel sheet may be subjected to temper rolling or pickling to remove scale formed on the surface. EXAMPLES
[0068] Molten steel having the composition shown in Table 1 was melted in a converter and cast at the rotation speed shown in Table 2 by a continuous casting method to produce a steel slab as a steel material. The obtained steel material was heated to the heating temperature shown in Table 2, and then the heated steel material was subjected to hot rolling consisting of rough rolling and finish rolling to produce a hot-rolled steel sheet. The finish rolling end temperature in the hot rolling was as shown in Table 2. Next, the obtained hot-rolled steel sheet was cooled under the conditions of the average cooling rate and cooling stop temperature shown in Table 2 (first cooling). The cooled hot-rolled steel sheet was coiled at the coiling temperature shown in Table 2, and the coiled steel sheet was cooled at the average cooling rate shown in Table 2 (second cooling) to obtain a high-strength steel sheet. After cooling, temper rolling was performed and pickling was performed. Pickling was performed at a temperature of 85°C using a hydrochloric acid aqueous solution with a concentration of 10 mass%.
[0069] [Table 1]
[0070] [Table 2]
[0071] Test pieces were taken from the obtained high strength steel plates, and the microstructures and mechanical properties were evaluated according to the procedures described below.
[0072] <Microstructure> From the obtained high-strength steel plate, a test piece for microstructure observation was taken so that the plate thickness cross section parallel to the rolling direction was the observation surface. The surface of the obtained test piece was polished and further corroded with an etchant (3% nital solution) to reveal the microstructure. Next, 10 fields of view were photographed at 1 / 4 of the plate thickness position using a scanning electron microscope (SEM) at a magnification of 5000 times to obtain SEM images of the microstructure. The obtained SEM images were analyzed by image processing to quantify the area ratios of upper bainite (UB), polygonal ferrite (F), lower bainite and / or tempered martensite (LB+TM). In addition, since it is difficult to distinguish upper bainite (UB), granular bainite (GB), fresh martensite (FM), and retained austenite phase (γ) using SEM, they were identified using electron beam reflection diffraction method, and the area ratios and average grain size of each were obtained. The area ratios of each microstructure and the average grain size of upper bainite measured are shown in Table 3. In addition, Table 3 also shows the total area ratio of upper bainite and granular bainite (B) and the total area ratio of fresh martensite and retained austenite phase (FM+γ).
[0073] [Table 3]
[0074] <Tensile test> From the obtained hot-rolled steel sheet, JIS No. 5 tensile test pieces (JIS Z 2201) were taken so that the tensile direction was perpendicular to the rolling direction, and the strain rate was 10 -3 A tensile test was carried out in accordance with the JIS Z 2241 standard, which specifies a tensile strength of 980 MPa or more per s in order to determine the tensile strength and uniform elongation. In the present invention, a tensile strength of 980 MPa or more was considered to be acceptable. A uniform elongation of 6.0% or more was considered to be excellent ductility.
[0075] <Plane bending fatigue test> Test pieces with the dimensions and shape shown in Figure 1 were taken from the obtained hot-rolled steel sheets so that the longitudinal direction of the test pieces was perpendicular to the rolling direction, and a plane bending fatigue test was carried out in accordance with the provisions of JIS Z 2275. The stress loading mode was a stress ratio R = -1 and a frequency f = 25 Hz. The load stress amplitude was changed to six stages, and the stress cycle up to fracture was measured, and an SN curve was obtained. 6 In the present invention, when the value obtained by dividing the fatigue limit by the tensile strength obtained in the tensile test is 0.50 or more, the fatigue property is evaluated as excellent.
[0076] <Punching ability evaluation> Test pieces (size: t (plate thickness) × 30 mm (width) × 30 mm (length)) were taken from the obtained hot-rolled steel plate. A punched hole was formed in the center of the taken test piece by punching with a cylindrical punch of 10 mmφ at three or more clearances including 10% and 20% within the clearance range of 10 to 20%. The clearance is the percentage [%] of the plate thickness of the test piece. When no cracks, chips, brittle fracture surfaces, or secondary shear surfaces were visually observed on the end surface of the punched hole, it was evaluated as having excellent punchability (○), and when these were confirmed, it was evaluated as ×.
[0077] <Hardness measurement> Hardness measurement samples were taken from the obtained high-strength steel plate so that the plate thickness cross section parallel to the rolling direction was the hardness measurement cross section, and the hardness at 1 / 2 the plate thickness position (Hv1) and the hardness at 1 / 4 the plate thickness position (Hv2) were measured. The Vickers hardness measurement conditions were a load of 100g and a holding time of 10s. Measurements were taken at five points in the ±1 / 20 plate thickness region at measurement intervals of 250μm or more, and the average was calculated.
[0078] Next, the difference between the obtained Hv1 and Hv2 (|Hv1-Hv2|) was evaluated by calculating the percentage relative to 0.3 times the value of the tensile strength obtained in the tensile test.
[0079] The examples of the invention are all high-strength steel sheets having a tensile strength of 980 MPa or more and excellent ductility, fatigue strength and punchability, whereas the comparative examples outside the scope of the present invention do not achieve a tensile strength of 980 MPa or more, or do not achieve excellent ductility, fatigue strength and punchability.
Claims
1. In mass percent, C: 0.04-0.18%, Si: 0.1 to 2.5%, Mn: 1.0 to 3.0%, P: 0.1% or less, S: 0.01% or less, Al: 0.010 to 1.0% and N: 0.01% or less Contains The remainder is Fe and unavoidable impurities. The microstructure is mainly composed of bainite phase consisting of upper bainite and granular bainite with an area ratio of 85% or more. The area ratio of a hard second phase including fresh martensite and / or retained austenite phase is less than 15%; In the bainite phase, the area ratio of granular bainite to the area ratio of upper bainite is 5% or more and 40% or less, The difference |Hv1-Hv2| between the hardness Hv1 at 1 / 2 the sheet thickness position and the hardness Hv2 at 1 / 4 the sheet thickness position is 30% or less with respect to 0.3TS, where Hv1 and Hv2 are Vickers hardness (Hv), and TS is tensile strength (MPa); The high-strength steel plate has an average crystal grain size of the bainite phase of 7 μm or less.
2. The high-strength steel plate according to claim 1, further comprising, in addition to the above-mentioned component composition, one or more of groups a to e in mass%. Group a: V: 0.005-0.5%, Ti: 0.005 to 0.2%, and Nb: 0.005 to 0.1%. One or more selected from the following: Group b: Cu: 0.005 to 0.5%, Ni: 0.005 to 0.5%, Cr: 0.005 to 1.0%, and Mo: 0.005 to 0.5%, one or more selected from the following: Group c: B: 0.0002 to 0.005%, Group d: Sb: 0.001 to 0.1%; and Sn: 0.001 to 0.1%. One or two selected from the following: Group e: Ca: 0.0001-0.005%, Mg: 0.0001 to 0.005%, and REM: 0.0001 to 0.005%, one or more selected from the following:
3. A method for producing a high strength steel plate according to claim 1 or 2, A molten steel material having the above-mentioned composition is cast while being rotated in a horizontal plane relative to a mold at a rotation speed of 10 cm / s or more by an induction electromagnetic stirrer; The obtained steel material is heated to 1150°C or higher, The heated steel material is roughly rolled into steel plates, The steel sheet is finish-rolled under the condition of a finish rolling end temperature of (RC-50)°C or more and (RC+100)°C or less, The steel sheet after the finish rolling is cooled under the conditions of a time from the end of the finish rolling to the start of cooling: 2.0 s or less, an average cooling rate on the surface up to Bs: 30 ° C. / s or more, a residence time at a temperature of (Bs-100) ° C. or more and Bs ° C. or less: 3.0 s or more and 10.0 s or less, and a cooling stop temperature: (Bs-250) ° C. or more and (Bs-100) ° C. or less, The cooled steel sheet is coiled under the condition of a coiling temperature of (Bs-250)°C or more and (Bs-100)°C or less, A method for producing high strength steel plate, comprising cooling to (Bs-400)°C or lower at an average cooling rate of 1°C / s or less. Here, RC and Bs are defined by the following equations (1) and (2), respectively. RC (℃) = 750 + 120 x C + 100 x N + 10 x Mn + 250 x Ti + 5000 x B + 10 x Cr + 50 x Mo + 750 x Nb + 150 x V... (1) Bs (℃) = 830-270 x C-90 x Mn-70 x Cr-37 x Ni-83 x Mo-20 x Cu... (2) Here, each element symbol in the above formulas (1) and (2) represents the content (mass %) of each element, and when no element is contained, it is set to 0.
Citation Information
Patent Citations
Hot-rolled high-strength steel strip with high hole expansion ratio
JP2023510137A
High strength and high toughness steel plates with low yield ratio and high uniform elongation and the method for preparation of the same
KR1020110116756A
Hot rolled steel sheet excellent in moldability, fracture characteristic and fatigue characteristic, and method for producing the same
JP2014031560A
Hot rolled steel sheet and production method therefor
JP2015214718A